Shisham mortality in Bihar extent and causes - and O.P. CHATURVEDI*, DAYARAM, M. KUMAR, S. SHARMA (Indian Phytopathology, 2003)
Twenty districts of North Bihar were surveyed to study the extent and causes of shisham mortality. Highest disease incidence was recorded in Araria district (80.0%) followed by Katihar (78.0%). Lowest disease incidence (35.4%)was recorded in Darbhanga followed by Khagaria (41.6%).60.5% disease was recorded in plants having 51-100 cm girth followed by plants 101-150cm girth (48.7%). Waterlogged condition aggravated the disease incidence. Fusarium solani 1. sp. dalbergiae has been confirmed as the pathogen.